ACHIEVEMENTS DISPARITY AMONG JOB SEEKERS IN A UNIVERSITY SETTING - Femi, Ogunsola (International Journal of Research -GRANTHAALAYAH, 2018)
The study investigated whether (i) the sex of job seeker has any appreciable impact on their performances on an aptitude test; (ii) the certificate obtained by the job seekers influenced their performances on an aptitude test; (iii) the scores of the job seekers in terms of their sex and certificate worth are homogeneous. Two hundred and ten (210) qualified WASC/GCE and OND/NCE job seekers made up of 120 male and 90 female were subjected to a 30 – item aptitude test. Their scores were analysed using a t – test and ANOVA at 0.05 level of significance. Results showed that there is a significant difference in the performances of job seekers by sex in favour of the male participants. Also, there is a significant difference in the performances of the job seekers in terms of their certificate worth in favour of the OND/NCE holders. The scores of the job seekers in terms of their sex and certificate worth were found to be significant and homogeneous and this was in favour of the male applicants and the OND/NCE holders. The implication of these findings is that experience in terms of certificate worth and sex of the individuals coupled with determination play significant role in any competitive examination. Employers of labour should always engaged good and qualified candidates for jobs without prejudice to sex and quota system to make room for efficiency.